Numerical Investigation of the Combined Influence of Shield Tunneling and Pile Cutting on Underpinning Piles - Wang, Ning; Jiang, Yalong; Geng, Daxin; Huang, Zhanjun; Ding, Haibin (Frontiers in Earth Science, 2022)
In this study, the combined influence of shield tunneling and the old pile cutting process on underpinning piles is investigated through finite element method (FEM) modeling based on a shield tunnel project in Nanchang Metro Line 2, China. Numerical models have been developed to analyze the influence of intersection angles and the vertical distance between the underpinning foundation and tunnels on the mechanical responses of underpinning piles during tunnel excavation. Simulation results show that the bending moment of the underpinning piles decreases with increasing vertical distance between the pile and tunnel, and is inversely proportional to the intersection angle between the underpinning beam and tunnel. In addition, the maximum pile bending moment occurs in the buried depth of the tunnel axis, indicating a high risk of damage in this part. According to the simulation results, more attention should be given to the underpinning piles in case a small vertical distance and intersection angle are encountered.